Identifikasi Penyakit Diabetes Millitus Menggunakan Jaringan Syaraf Tiruan Dengan Metode Perambatan-Balik (Backpropagation) - Sriyanto Sriyanto; Sutedi Sutedi (IIB Darmajaya, 2010)
Diabetes Melitus (DM) is dangerous disease that affect many of the various layer of work society. This disease is not easy to accurately recognized by the general society. So we need to develop a system that can identify accurately. System is built using neural networks with backpropagation methods and the function activation sigmoid. Neural network architecture using 8 input layer, 2 output layer and 5 hidden layer. The results show that this methods succesfully clasifies data diabetics and non diabetics with near 100% accuracy rate. Keyword : Neural Network, Backpropagation, diabets